Mudanças no uso e cobertura da terra na bacia hidrográfica do Ribeirão Bonito, municípios de Avaré e Itatinga-SP - Zanata, Juliana Marina [UNESP] (2014)
In order to monitor and minimize environmental problems, GIS, combined with GIS techniques, have important potential application since they allow the obtaining, storing and manipulating large amounts of data and information, as well as the cartographic representation of these variables, enables the decision-making with greater security. The objective of this study was to map land uses of Ribeirão Bonito watershed in two different seasons (1962 and 2010) and analyze the changes in the area looking for the characterization of environmental impacts identified in the basin through the use of techniques GIS. To achieve the mappings were used in 1962 aerofotografias and SPOT satellite images of 2010. The watershed of Ribeirão Bonito is located in the municipalities of Itatinga and Avare, in the southwest of the State of São Paulo and as most of this state had its colonization based on the rampant use of natural resources, a fact that eventually compromise the quantity and quality of these. The Land Change Modeler application contributed to understanding the dynamics present in the use and coverage of the basin. In the analyzed period was possible to notice the emergence of two classes of use, the permanent crop by planting oranges and forestry by planting eucalyptus. As for natural vegetation and other uses was possible spatialize the changes that occurred